A stable home‐base promotes allocentric memory representations of episodic‐like everyday spatial memory. (20th March 2020) - Broadbent, Nicola; Lumeij, Lucas Berend; Corcoles, Marta; Ayres, Alice I.; Bin Ibrahim, Mohammad Zaki; Masatsugu, Brittany; Moreno, Andrea; Carames, Jose‐Maria; Begg, Elizabeth; Strickland, Lauren; Mazidzoglou, Theofilos; Padanyi, Anna; et al.
Abstract: A key issue in neurobiological studies of episodic‐like memory is the geometric frame of reference in which memory traces of experience are stored. Assumptions are sometimes made that specific protocols favour either allocentric (map‐like) or egocentric (body‐centred) representations. There are, however, grounds for suspecting substantial ambiguity about coding strategy, including the necessity to use both frames of reference occasionally, but tests of memory representation are not routinely conducted. Using rats trained to find and dig up food in sandwells at a particular place in an event arena (episodic‐like 'action‐where' encoding), we show that a protocol previously thought to foster allocentric encoding is ambiguous but more predisposed towards egocentric encoding. Two changes in training protocol were examined with a view to promoting preferential allocentric encoding—one in which multiple start locations were used within a session as well as between sessions; and another that deployed a stable home‐base to which the animals had to carry food reward. Only the stable home‐base protocol led to excellent choice performance which rigorous analyses revealed to be blocked by occluding extra‐arena cues when this was done after encoding but before recall. The implications of these findings for studies of episodic‐like memory are that the representational framework of memory at the start of a recall trial will likely include a path direction in the egocentric case but path destination in the allocentric protocol. This difference should be observable in single‐unit recording or calcium‐imaging studies of spatially‐tuned cells. Abstract : How does the animal get to the reward? Remembering where (allocentric), or remembering the route (egocentric)? A new 'home‐base' training protocol in the event arena for episodic‐like everyday memory is shown definitively to utilise allocentric memory encoding (image courtesy of Tobias Bast). The finding has implications for behavioural and cognitive test of episodic‐like memory, and single‐unit recording studies of navigation system.